Heat shock proteins overexpressed in tumour cells and their relationship with ageing and cellular resistance to treatment - Burgos-Molina, Antonio Manuel; Peinado-Ruiz, Isabel C.; González Vidal, Alejandro; Ruiz-Gómez, Miguel José (My University, 2022)
The increase in the concentration of HSP in tumour cells produces an increase in the capacity for replication, migration, and drug resistance. HSP and HSF1 factor are involved in the etiology of breast cancer. The overexpression of HSP27, HSP40, HSP70, HSP90 and HSF1 in breast cancer leads to increased multidrug resistance, inhibition of apoptotic cell death, and acceleration of tumour progression. Furthermore, the presence of very high levels of HSP90 resulted in a ductal type carcinoma.
Keywords: Células humanas - Investigación; Heat shock proteins overexpressed in tumour cells; Ageing and celular resistance to treatment